AN INTERPERSONAL MEANING ANALYSIS OF AHOK’S BLASPHEMY CASE IN ONLINE NEWS PORTALS - Teti Kartika; Marwito Wihadi (University of Kuningan, 2018)
This research presents an interpersonal meaning analysis of two online news concerning Ahok’s blasphemy case in the two online news portals. The two selected news coming from The Jakarta Post and Republika.co.id were analyzed to find out the mood types and to describe the underlying reason of the news from the differences of modality system. This descriptive qualitative research involved the analysis of mood and modality types of clauses identified. As results, it shows that the interpersonal meaning was applied. Yet, not all mood or modality types appeared in the two online news. There is only one mood and one modality type appeared, namely indicative which is declarative type and modalization which is probability type. Therefore, it can be concluded that both writers used the same mood and modality types in the online news of Ahok’s blasphemy case as well as their interpersonal meaning are determined by contextual factors such as the aims or needed in giving information about the news event of Ahok’s blasphemy case in Indonesia.Keywords: Interpersonal meaning, Ahok, blasphemy case, online news